Readiness Analysis for Regional Public Service Agency Implementation Focusing on Substantive and Technical Requirements (A Case Study of UPTD Balai Kawasan Konservasi Perairan Daerah, North Maluku Province) - Siti Nur Maryanti; Sutoyo Sutoyo; Zuhrotun Zuhrotun (AIBPM Publisher, 2024)
This study aims to analyze the readiness of the UPTD Balai Kawasan Konservasi Perairan Daerah (BKKPD) of North Maluku Province in implementing a Regional Public Service Agency (BLUD) by examining the fulfillment of substantive and technical requirements. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The results indicate that BKKPD has met the substantive requirements, which include operational duties and the provision of semi-commercial services for the public. The technical requirements in the eligibility criteria have also been met, covering the potential for improving service delivery effectiveness and technical specifications directly related to public services. However, in the potential criteria, further study is needed to identify potential services that BKKPD can develop after transitioning to BLUD status. The financial management flexibility provided by BLUD is expected to support BKKPD in performing its duties more responsively and adaptively to conservation needs and public services. These findings are expected to assist the North Maluku Provincial Government in assessing BKKPD's readiness to transform into a BLUD and enhance the benefits of its services to the community.